Peningkatan Tata Krama Pergaulan Melalui Layanan Orientasi Pada Siswa SMP - Suminto Suminto (Journal Prakarsa Paedagogia, 2018)
The purpose of this study was to determine the improvement of student manners through orientation services in guidance and counseling. The research design was quasi-experimental using 40 research subjects in Kayen Secondary School. The result is that the hypothetical testing obtained by manners through information services is rxy = 0.503, with a significant level of 5%, N = 40, with r table 0.312 so that it can be concluded that orientation services can improve student etiquette.